Live Plague Vaccine Development: Past, Present, and Future - Andrey P. Anisimov; Anastasia S. Vagaiskaya; Alexandra S. Trunyakova; Svetlana V. Dentovskaya (Vaccines)
During the last 100 years, vaccine development has evolved from an empirical approach to one of the more rational vaccine designs where the careful selection of antigens and adjuvants is key to the desired efficacy for challenging pathogens and/or challenging populations. To improve immunogenicity while maintaining a favorable reactogenicity and safety profile, modern vaccine design must consider factors beyond the choice of target antigen alone. With new vaccine technologies currently emerging, it will be possible to custom-design vaccines for optimal efficacy in groups of people with different responses to vaccination. It should be noted that after a fairly long period of overwhelming dominance of papers devoted to subunit plague vaccines, materials devoted to the development of live plague vaccines have increasingly been published. In this review, we present our opinion on reasonable tactics for the development and application of live, safe, and protective human plague vaccines causing an enhanced duration of protection and breadth of action against various virulent strains in vaccination studies representing different ages, genders, and nucleotide polymorphisms of the genes responsible for immune response.